2018
DOI: 10.1002/ss.20249
|View full text |Cite
|
Sign up to set email alerts
|

History of Sexual Violence in Higher Education

Abstract: In this chapter, we describe the history of sexual violence as it pertains to postsecondary institutions, focusing on social movements, research, and policy, and their implications for higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…According to the students that replied to the questionnaire, nearly 8% of them experienced sexual violence—more specifically forced sex—from university staff, other students or patients. Awareness of sexual violence in the academic routine gradually improved over the last 30 years . With research dedicated to the field, the scientific literature clearly pointed out that sexual violence became endemic in university campuses .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the students that replied to the questionnaire, nearly 8% of them experienced sexual violence—more specifically forced sex—from university staff, other students or patients. Awareness of sexual violence in the academic routine gradually improved over the last 30 years . With research dedicated to the field, the scientific literature clearly pointed out that sexual violence became endemic in university campuses .…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of sexual violence in the academic routine gradually improved over the last 30 years. 21 With research dedicated to the field, the scientific literature clearly pointed out that sexual violence became endemic in university campuses. 22 This panorama is global.…”
Section: Sexual Violencementioning
confidence: 99%
“…It is against this background that the form and content of violence reduction programs began to emerge. For example, the programs were designed and implemented without time for pilot work or systematic program evaluation prior to deployment (Coker et al., ; Jessup‐Anger, Lopez, & Koss, ). They were constructed out of existing theoretical approaches that were assumed a priori to be relevant.…”
Section: Bystander Informed Violence Reduction Programsmentioning
confidence: 99%
“…However, postsecondary institutions continue to grapple with effectively addressing the problem (Black et al, 2011;Fedina et al, 2018;James, 2017;Richards, 2016). Postsecondary institutions face multiple barriers, such as institutional leadership's propensity to systematically underestimate the issue (Jessup-Anger et al, 2018;Straumsheim, 2015). Indeed, a survey of 647 college presidents found that just 32% either strongly agreed or agreed that sexual assault was prevalent at U.S. colleges and universities (Jaschik & Lederman, 2015, p. 18).…”
mentioning
confidence: 99%